Going beyond supplier diversity to economic Inclusion:Where are we now and where do we go from here?. Issue 2 (March 2022) - Sordi, Andrea; Tate, Wendy L.; Huang, Feigao
Abstract: Supplier diversity is not a new concept but has increased in urgency due to racial unrest and social polarization across the globe. As culture shifts globally, demanding more diversity and inclusion in businesses, companies are having to rethink their overarching values and strategies. Supplier diversity programs foster more inclusive relationships with diverse and underrepresented populations of suppliers to produce both economic and social impact. Researchers have shown if managed effectively, a diverse and inclusive supply base can help organizations reduce risk, enhance brand image, and increase innovation and flexibility. The intent of this Notes and Debates article is to introduce and define supplier diversity, showing how an economically inclusive supplier diversity program enhances organizational benefits and provides greater economic and social benefits. A secondary intent is to begin the dialogue on the benefits of transitioning from traditional supplier diversity programs to fully embedded economic inclusion models. What is the purpose behind the transition? Is more supplier diversity necessarily better? What enablers or capabilities may be needed to evolve from a traditional supplier diversity program to a strategically positioned economic inclusion mindset? Suggestions are made about embedding key enablers within an organizational structure so that companies can mature in supplier diversity efforts and drive stronger social and economic value. This Notes and Debates piece uses support from ongoing research efforts that include interviews with companies engaged in supplier diversity programs and several supplier diversity councils. Some initial observations and remarks are incorporated in the text to help illustrate how to move from supplier diversity to economic inclusion. The enablers that help move from traditional diversity programs to economic inclusivity appear to mature and develop over time. Some organizations remain in the early, more traditional phases while others have dynamic ecosystems that have developed to support this transition. Highlights: Supplier diversity has increased in urgency due to racial unrest and social polarization across the globe. A diverse and inclusive supply base can bring economic and social benefits to buying companies. Transition from traditional supplier diversity programs to an economic inclusion mindset is necessary.